Attitudes towards income inequality and trust: an analysis by income class in Poland - Szczepaniak , Małgorzata; Bentkowska, Katarzyna (Economics and Business Review, 2025)
Increasing income inequality has raised concerns about its effects on social cohesion, yet the subjective dimension of inequality and its relation to trust remain underexplored. This article investigates how attitudes toward income inequality relate to generalized and institutional trust across income classes in Poland, a post-socialist country characterized by strong anti-inequality sentiment and low trust levels. Using data from the European Values Study (N = 1,352), we apply an economic stratification framework with five income classes, combined with nonparametric tests and logistic regression. Results show that acceptance of inequality increases with income, with the sharpest contrasts between low- and high-income classes, while middle strata remain relatively homogeneous. Generalized trust rises with income, whereas institutional trust follows more complex, non-linear patterns. Crucially, links between trust and inequality attitudes are class-specific: generalized trust in strangers legitimizes inequality overall, while generalized trust in relatives has divergent effects across lower- and upper-middle income groups.